2021
DOI: 10.1111/cpr.13157
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 promotes mRNA degradation via YTHDF1‐AGO2 interaction and phase separation

Abstract: Objectives YTHDF1 is known as a m 6 A reader protein, and many researches of YTHDF1 focused on the regulation of mRNA translation efficiency. However, YTHDF1 is also related to RNA degradation, but how YTHDF1 regulates mRNA degradation is indefinite. Liquid‐liquid phase separation (LLPS) underlies the formation of membraneless compartments in mammal cells, and there are few reports focused on the correlation of RNA degradation with LLPS. In this research, we focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…As is well known, the complex mechanisms of m6A regulation coordinated by methyltransferases (writers), demethylases (erasers), and reader proteins [ 24 ]. At present, several m6A readers (YTHDF1, YTHDF2, YTHDF3, and YTHDC1) have been confirmed to be involved in RNA degradation [ 22 , 25 29 ]. Thus, RNA pull-down assay was performed and these protein were detected by western blot.…”
Section: Resultsmentioning
confidence: 99%
“…As is well known, the complex mechanisms of m6A regulation coordinated by methyltransferases (writers), demethylases (erasers), and reader proteins [ 24 ]. At present, several m6A readers (YTHDF1, YTHDF2, YTHDF3, and YTHDC1) have been confirmed to be involved in RNA degradation [ 22 , 25 29 ]. Thus, RNA pull-down assay was performed and these protein were detected by western blot.…”
Section: Resultsmentioning
confidence: 99%
“…For shRNA knockdown experiments, independent shRNAs targeting a different region of MCM4 RNA were constructed using a pLKO.1 vector (Addgene), and the oligo sequences were provided in follow. Lenti-viruses were generated according to the manufacture protocol as previously documented ( 23 ) and indicated cells were infected by viruses twice with 48 h and 72 h viral supernatants containing 4 μg/mL polybrene, and stable cell lines were established by appropriate puromycin selection. The two independent MCM4 targeting sequences are: shRNA#1, 5’-GGGTGGAGATGGACCGCGGCC-3’; shRNA#2, 5’-GCCTTGATGAAGAAGCAGAAC-3’.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of BRD4 coactivator LLPS condensates can be promoted by YTHDC1/m6A-eRNA phase separation condensate co-mixes 99 . In addition, mRNA degradation can be promoted by YTHDF1 phase separation and the interaction of YTHDF1-AGO2 100 . These studies showed that the composition of intracellular LLPS transcriptome can be regulated by the distribution and number of m6A sites in mRNA, which indicates that phase separation can control the cellular characteristics of m6A modified mRNA.…”
Section: The Regulation Of Llps Condensatesmentioning
confidence: 99%